Inelastic vibrational dynamics of CS in collision with H2 using a full-dimensional potential energy surface. Issue 45 (8th November 2018) - Yang, Benhui; Zhang, P.; Qu, C.; Stancil, P. C.; Bowman, J. M.; Balakrishnan, N.; Forrey, R. C.
Abstract : A six-dimensional potential energy surface for the CS–H2 system was computed using high-level ab initio theory and fitted using a hybrid invariant polynomial method. Quantum close-coupling scattering calculations have been carried out for rovibrational quenching transitions of CS induced by H2 . Abstract : We report a six-dimensional (6D) potential energy surface (PES) for the CS–H2 system computed using high-level electronic structure theory and fitted using a hybrid invariant polynomial method. Full-dimensional quantum close-coupling scattering calculations have been carried out using this potential for rotational and, for the first time, vibrational quenching transitions of CS induced by H2 . State-to-state cross sections and rate coefficients for rotational transitions in CS from rotational levels j 1 = 0–5 in the ground vibrational state are compared with previous theoretical results obtained using a rigid-rotor approximation. For vibrational quenching, state-to-state and total cross sections and rate coefficients were calculated for the vibrational transitions in CS( v 1 = 1, j 1 ) + H2 ( v 2 = 0, j 2 ) → CS( v 1 ′ = 0, j 1 ′) + H2 ( v 2 ′ = 0, j 2 ′) collisions, for j 1 = 0–5. Cross sections for collision energies in the range 1 to 3000 cm −1 and rate coefficients in the temperature range of 5 to 600 K are obtained for both para -H2 ( j 2 = 0) and ortho -H2 ( j 2 = 1) collision partners. Application of the computed results in astrophysics is also discussed.